A Pragma-Stylistic Analysis of President Prabowo Subianto’s Speech at the 2024 World Government Summit - Nazreensyah, Fabian Putra; Siahaan, Daniel Fernando; Anargya, Hafwen; Hutapea, Vimelia Fratiwi; Rangkuti, Rahmadsyah (Universitas Nurul Jadid, 2025)
This study examines the pragma-stylistic features of President Prabowo Subianto’s speech at the 2024 World Government Summit. Using Speech Act Theory by Austin (1962) and Searle (1969), the analysis identifies and categorizes different types of speech acts employed in the speech. The study focuses on how language functions as a strategic tool in political discourse, shaping perceptions and reinforcing ideological positions. A total of 57 sentences were extracted and analyzed to determine the frequency and distribution of speech act categories. The findings reveal that representative speech acts dominate the speech (57.89%), followed by expressive (15.79%), commissive (14.04%), directive (7.01%), and declarative (5.27%) acts. These results highlight the rhetorical strategies used by President Prabowo to assert political commitments, express national priorities, and engage with a global audience that revolves around trust with other country. This study enhances insight into how speech acts influence international discourse and contribute to the field of political communication.